The effectiveness of students’ preparation in physical training at the universities of various departments - Anvar A. Akhmatgatin; Vladislav Y. Lebedinsky; Gennady K. Khomyakov; Mikhail D. Kudryavtsev; Alena G. Galimova; Tatyana L. Kamoza; Evgeniy V. Panov; Vladimir A. Kuzmin; Alexey V. Gaskov; Leonid K. Sidorov; Sergey A. Doroshenko (Physical Education of Students, 2020)
Purpose. To make a comparative analysis and evaluate the effectiveness of physical exercises in a technical university and departmental university of the Ministry of Internal Affairs of Russia.